(untitled) - Nguyễn, Thị Thu Hiền (Cần Thơ, 2011)
This research aims at exploring the needs of English for Specific Purpose (ESP) to police students at Can Tho Police College. The research is a survey following the descriptive approach design. The participants attitudes towards the needs of ESP were examined by questionnaires, structured interview and opened interview
Keywords: Ngôn ngữ tiếng Anh,English language; Dạy và học,Study and teaching